2021
DOI: 10.1021/acsbiomaterials.1c00563
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Methacrylate-Functionalized Betulin Derivatives as Antibacterial Comonomer for Dental Restorative Resins

Abstract: Secondary caries is the primary cause of composite restoration failures, resulting from marginal leakage and bacterial accumulation in the oral environment. Antibacterial dental composites, especially antibacterial monomers, have emerged as a promising strategy to inhibit secondary caries, which is pivotal to prolonging the lifespan of dental restorations. In this work, monomethacrylate- and dimethacrylate-functionalized betulin derivatives (M1Bet and M2Bet) were synthesized via an esterification reaction and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 55 publications
1
31
0
1
Order By: Relevance
“…Interestingly, the viabilities of either cell type for two electrospun fibrous mats were greater than ∼92% on average, indicating their excellent biocompatibility for potential biomedical applications. These results are in consistent with previous reports. , …”
Section: Resultssupporting
confidence: 94%
See 3 more Smart Citations
“…Interestingly, the viabilities of either cell type for two electrospun fibrous mats were greater than ∼92% on average, indicating their excellent biocompatibility for potential biomedical applications. These results are in consistent with previous reports. , …”
Section: Resultssupporting
confidence: 94%
“…It is found that both mono- and dual-functionalized betulin monomers exhibit less dense colonies than betulin, suggesting they are capable of inhibiting the growth of bacteria. Betulin moieties in polymeric materials can maintain their biological activity and contribute to the antimicrobial properties of the polymers. , Herein, the antimicrobial properties of the fibrous mats were characterized using colony formation counting with E. coli (Gram-negative bacteria), S. aureus (Gram-positive bacteria), and C. albicans (fungi), and the results are shown in Figure . It was found that the count for viable colonies of E. coli decreased for both mats after 24 h. Interestingly, the colony numbers dramatically decreased for S. aureus and C. albicans , indicating a better antibacterial activity against Gram-positive bacteria and fungus.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, stereochemical strategies have received special attention because of their safe, nontoxic, nonrelease, and long-term advantages. The theoretical basis of this antibacterial strategy is the selective recognition by microorganisms of chiral terpenoid molecules (borneol or menthol). The chiral terpenoid molecule-grafted surfaces and polymers exhibited excellent antimicrobial (bacterial and fungal) properties. The related studies have shown that the antimicrobial adhesion performance based on stereochemistry is closely related to the number of grafted chiral molecules, , indicating that the increase of the modification density of stereochemical terpene molecules will help to improve the antimicrobial adhesion properties of modified PET. Menthol is a typical terpenoid molecule whose modified materials have emerged as candidates for antimicrobial adhesion. , Compared with borneol, menthol is more likely to produce various derivatives due to its low spatial resistance and high reactivity. , Therefore, skeleton modification of PET with the menthol moiety should be an appropriate method to impart antimicrobial adhesion properties to PET.…”
Section: Introductionmentioning
confidence: 99%